Water Service as a Means of Ensuring a Public Good and the River Basin Management Plan in the Context of Procedures for General and Specific Acts: EU Institutions Against the Background of Professor Kasznica’s Work (Contemporary Central & East European Law, 2024)
The subject of the article is the institutions of European law as defined by the Water Framework Directive. They are mentioned in the title of the article. It is important that both of these institutions are described and analysed in the context of Professor Kasznica's scientific output concerning the manner of ensuring the use of a public thing (here, the water service) and in the context of the procedures of applying general and specific acts (here, the river basin management plan). It is shown that the scientific theses of the professor remain valid also in the context of the regulations of European administrative law.